Підключення мікроконтролера до локальної мережі за допомогою модуля на мікросхемі ENC28J60 - Славгородський, Я. В.; Чумак, В. С. (ХНУРЕ, 2022)
Often, microcontrollers need access to the Internet, a local network. This can be useful, for example, for building a smart home, telemedicine systems [1, 2], creating weather stations, installing a simple web server, and much more. All this can be provided by the ENC28J60 Ethernet module. The ENC28J60 Mini Ethernet Module is a compact version of the ENC28J60 Ethernet Module. The board is designed to connect devices based on Arduino, AVR, PIC, ARM, etc. to an Ethernet network.
Keywords: ENC28J60; підключення мікроконтролера